Effect of Proteus Mirabilis Biofilm Formation on Antibiotic Resistance in Urinary Tract Infections - Mohammed, Manal Dheyaa (American Journal of Biomedicine and Pharmacy, 2026)
Introduction & objectives: Proteus mirabilis is a frequent cause of UTIs in women. Its ability to produce biofilms increases the resistance against several antibiotics and makes its treatment even more challenging. The main objectives of this study were to estimate distribution of P. mirabilis in UTI infected female patients, determine the antibiotic resistance patterns, evaluate biofilm formation and explore association between biofilm production and multidrug resistance. Materials & Methods: In total, 175 urine samples were taken from female patients in Kirkuk hospitals. The isolates were characterized by morphology, biochemical testsand VITEK 2 system. Antibiotics sensitivity profile was determined using the Kirby-Bauer disk diffusion technique for 14 antibiotics. Biofilm production was measured by 96-well microtiter ELISA). Results: Out of 175 samples, 87 (49.7%) were positive for P. mirabilis. All isolates were confirmed by biochemical tests and VITEK 2. Furthermore, molecular confirmation revealed that all 17 selected isolates (100.0%) carried the 16S rRNA gene, confirming their identity as P. mirabilis. Resistance was highest against ampicillin (78%), cefotaxime (65%), and trimethoprim-sulfamethoxazole (60%), while amikacin (90%) and meropenem (88%) were largely effective. MDR isolates were 36 (41.4%), XDR 12 (13.8%), and EDR 3 (3.4%). Biofilm formation was detected in 75 isolates (86.2%), with 25 strong (28.7%), 30 moderate (34.5%), 20 weak (23%), and 12 non-producers (13.8%). Strong and moderate biofilm producers showed higher MDR/XDR rates (88% and 83%, respectively). Conclusions: P. false mirabilis is a common isolate in female UTIs in Kirkuk, and biofilm formation dramatically increases drug resistance. These results highlight the need to take account of biofilm-based resistance in clinical treatments.